Specialized Medical Weight Management Intervention for High-Risk Obesity - Gitanjali Srivastava; Chelsea Paris; Jessica Johnson; Emma Barnes; Brittany L. Cunningham; C. J. Stimson; Kevin D. Niswender; Sabrina J. Poon (Journal of Health Economics and Outcomes Research)
**Background:** Bundled payments are services rendered at pre-determined costs with the goal of providing high value care. Our institution’s Episodes of Care team partnered with its tertiary care obesity center to design a novel medical weight management bundle for employers that would collectively deliver high value obesity services.